Launch of the AWARE Platform and the National Dialogue on Sensitizing Anticipatory Action in Senegal, Dakar, Senegal, 11-12 October 2023 - Sambou, M. H. A.; Okem, Andrew Emmanuel; Jampani, Mahesh; Attoh, Emmanuel M. N. A. N.; Amarnath, Giriraj (International Water Management Institute, 2023)
In October 2023, IWMI organized a workshop with the National Agency of Civil Aviation and Meteorology (ANACIM) and the support of Alliance Bioversity-CIAT on behalf of the CGIAR Initiative on Climate Resilience, ClimBeR, to launch the AWARE Platform in Senegal. This platform aims to provide early warning, early action, and finance and introduce a dialogue on sensitizing anticipatory action to mitigate climate risks. The workshop brought together 53 key stakeholders, including government officials, local and international NGO representatives, academic staff, and private sector experts. These stakeholders had diverse expertise in food security, nutrition, agriculture, environment, and disaster risk management. The workshop focused on four main sessions, including group activities and case studies, where participants shared their ideas, knowledge, and experiences to help improve the AWARE platform. The workshop highlighted the importance of cross-sectoral collaboration and diverse stakeholder engagement, particularly with government institutions, to mitigate disaster management risks in Senegal.